1996
DOI: 10.1136/jamia.1996.97035025
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of a Computer-based Physician Workstation in an Outpatient Setting: Implementation Barriers to Outcome Evaluation

Abstract: The intervention physicians did not use the PWS frequently enough to influence information-seeking behavior, health outcomes, or cost. The study design did not determine whether the poor usage resulted from satisfaction with the control system, problems using the PWS intervention, or the functions provided by the PWS intervention. Evaluative studies should include provisions to improve the chance of successful implementation as well as to yield maximum information if a negative study occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 8 publications
0
31
0
Order By: Relevance
“…Twenty-four RCTs [60-62,65-67,69,71-76,78,80-89] had been included in the previous version of our review [2]. Study authors confirmed or supplemented our data extraction for 53 of 65 included studies (82%) [16-20,23,25-33,35-39,42-45,47-49,53-55,57,58,60-62,65-72,74-76,78,81,83-86,88]. Forty-seven included studies contribute outcomes to this review as well as other CCDSS interventions in the series; four studies [49,56,76,80] to four reviews, 16 studies [16,19,21,28,40,44,45,53,55,59,62,64,68,69,74,77-79,82,85,89] to three reviews, and 27 studies [20,22,23,26,27,29,31,32,34,35,39,41-43,46-48,50,52,54,60,63,66,70,72,75,81,86-88] to two reviews; but we focused here on drug prescribing-relevant outcomes.…”
Section: Resultsmentioning
confidence: 96%
“…Twenty-four RCTs [60-62,65-67,69,71-76,78,80-89] had been included in the previous version of our review [2]. Study authors confirmed or supplemented our data extraction for 53 of 65 included studies (82%) [16-20,23,25-33,35-39,42-45,47-49,53-55,57,58,60-62,65-72,74-76,78,81,83-86,88]. Forty-seven included studies contribute outcomes to this review as well as other CCDSS interventions in the series; four studies [49,56,76,80] to four reviews, 16 studies [16,19,21,28,40,44,45,53,55,59,62,64,68,69,74,77-79,82,85,89] to three reviews, and 27 studies [20,22,23,26,27,29,31,32,34,35,39,41-43,46-48,50,52,54,60,63,66,70,72,75,81,86-88] to two reviews; but we focused here on drug prescribing-relevant outcomes.…”
Section: Resultsmentioning
confidence: 96%
“…40 [1990-99, ambulatory care] Technical problems (15) "The slow speed makes [me] 'uneasy': kind of high stress just sitting there waiting for stuff to come up." 60 (7) "…59% said that they would find the prescribing support useful if it was integrated with their practice computer…" 72 [1990-99, ambulatory care] "…expressed the frustration that different software systems are difficult to integrate." 53 (7) "…nurses and providers displayed substantial confusion regarding delegation of responsibility for satisfying CRs (removing them from the due list)."…”
Section: Provider-related Factors (Table 4)mentioning
confidence: 99%
“…Similarly, automated clinical care protocols have been used in England (Herbert et al, 1995) and The Netherlands (Vissers et al, 1996a, b). The clinical practice setting has yet to incorporate the computer as a tool for clinical decisionmaking (Flanagan et al, 1995;Ireland, 1996;Rotman et al, 1996). Problems remain in existing software that deter physician acceptance, including physician downtime for data entry (Hammer et al, 1995), nonstandardized codes for clinician and computer interfacing (Johnson, 1996), perceived problems of maintaining patient and provider confidentiality (Immonen, 1996), protection of records integrity from data hackers (Von Solms, 1996), lack of portability of computer modules (Werner et al, 1995), and poorly designed workstations (Dayhoff et al, 1994).…”
Section: Commentmentioning
confidence: 99%